Assessment of current asset management practices of the selected active sustainable livelihood program associations (SLPA) in Bohol - Angelia, Cherry Jean, et.al.; Elanga, Angela Eunice; Gulle, Matt Erwin; Namoc, Kloie Edreane (b)
Abstract: Managing current assets is critical to microenterprises as it creates a trade-off between operating performance and liquidity. This study assesses the current asset management practices among selected active Sustainable Livelihood Program Associations (SLPAs) under the Microenterprise Development (MD) Track in the municipalities of Dauis and Panglao, Bohol. A quantitative descriptive research design was employed, utilizing complete enumeration and guided questionnaires to collect data relevant to the study's key research questions. Findings revealed notable strengths and weaknesses in the current asset management practices of SLPAs. Cash management, receivables, and inventory handling showed structured efforts, including regular budgeting, consistent tracking, and organized storage and recording practices. However, several gaps were identified, such as inadequate use of forecasting, infrequent updates to financial records, and inconsistent application of controls for credit and inventory. These weaknesses were compounded by the lack of clearly designated personnel for critical tasks, leading to overlapping responsibilities, inefficiencies in operations, and limited accountability. The absence of systematic role assignments also affected transparency, making it difficult to ensure accurate and reliable management of current assets. Recommendations include the adoption of structured budgeting processes, stricter credit policies, and clearly define roles and responsibilities to enhance operational effectiveness. It also highlights the need for the Department of Social Welfare and Development (DSWD) to provide financial literacy training, standardized asset management guidelines, and partnering with academic institutions that specialize in this related field. By addressing these deficiencies, SLPAs can strengthen internal controls, ensure transparency, and achieve better financial and economic outcomes for their communities.
CBA
Keywords: Financial management; Asset control